The Endemic Element in Flora of Dnieper Left-Bank Grass Steppe Depressions (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The article presents analysis of the endemic element in flora of Dnieper Left-Bank Grass Steppe of Ukraine. The basis of the endemic kernel of flora is formed by the Black Sea geographical elements. The endemic kernel consists of the local (Dnieper-Molochna) euendemics, confined and extensive hemiendemics. The endemic complex of the depressions includes 72 species. The endemism level is 14,60%. Cholorogically, the are the endemic flora of the depressions 4 florogenetical vectors (base types) Pannonian, Caspian, local Dnieper, and Sivash-Crimean which are clearly marked. The florogenetic connections of the territory are realized in concrete groups of the area, arealogic disjunctions, and vicarism of the endemic taxa or taxonomical complexes of this and adjoining phytochores. Vicarism of the neoendemics reflects the latitudinal-zonal connections of the depression flora of the Dnieper Left-Bank Grass Steppe, with flora of the Pannonian Lowland, the Dnieper Right-Bank Grass Steppe, and regions of the Sea of Azov, the Lower Don, the Caspian Sea, and Balkhash. Domination of the neoendemics and progressiveness of endemism of flora of the depressions mirror of geological youth of the territory studied, development of the Pontic and the local Low Dnieper floristic centres.
Keywords: endemic element, depressions, the Left-Bank Grass Steppe.